Effect of Catfish Culture Waste (Clarias sp.) on The Growth of Silk Worms (Tubifex sp.) - Maulana, Fachrurizal Amri; Cokrowati, Nunik; Scabra, Andre Rachmat (Jurnal Media Akuakultur Indonesia, 2023)
Silkworms, as natural food, have an essential role because they can stimulate fish growth. However, silkworms in nature are not always available all year round, so it is necessary to cultivate silkworms. Silkworms need a medium containing organic matter and inorganic matter for their growth. Catfish farming wastewater contains a lot of organic matter. This study aims to evaluate the effect of catfish farming waste (Clarias sp.) on the growth of silkworms (Tubifex sp.) in different initial biomasses. This research method uses the experimental method Complete Randomized Design with four treatments and three repeats. The treatment used is P1 = 15 grams of silkworms; P2 = 20 grams of silkworms; P3 = 25 grams of silkworms; and P4 = 30 grams of silkworms. For analyzing data use ANOVA with a 95% confidence level and the Lower Significance Difference test on SPSS. The results showed that the provision of catfish farming waste had a real influence on the growth of silkworms. Silkworms' absolute weight and biomass were highest in treatment four, which were 195.33 g and 0.112 g. Therefore, catfish farming waste has the potential to be used as raw material for silkworm feed.